MECHANISMS OF THE INCREASING OF THE PLATELETS FUNCTION AT CHRONIC CEREBRAL ISCHEMIA - Баринов Е. Ф.; Mamedaliyeva, S.; Баринова М. Е.; Твердохліб Т. А. (World of Medicine and Biology, 2014)
Established the possibility to increase the functional response hyporeactive platelets during stimulation in vitro with subthreshold dose of ADP and Epinephrine in patients of chronic cerebral ischemia (CCI). The study included 48 patients with diagnose of CIM 1-2 stage. Analysis of the functional state of platelets in vitro was carried out at the time of hospitalization prior to conservative therapy. Study was carried out on the aggregometer Chrono - Log (USA). Group of patients with baseline hyporeactivity (14,5 ± 2,6%) is sufficient heterogeneous (in the I-quartile is 5% and III -21%). Low initial response of platelets to Epinephrine and ADP was a consequence of the reduced secretion of endogenous ADP from the granules, i.e it is limited of the adaptive response of platelets. ADP-induced aggregation of platelets (EC50) indirectly reflects the force of adaptive response, which predetermines the possibility of summation of the Epinephrine and ADP effects. Determination of the mechanisms of platelets adaptation against the action of exogenous signals will expand tactics of pharmacological correction aimed at thrombogenesis prevention.